Integrasi Islamic Critical Thinking dalam Pendidikan Kontemporer: Upaya Meningkatkan Kecerdasan Berpikir Kritis Pelajar - Falaah, Muhammad Fajrul; Suryadin, Adin; Makmur, Makmur; Safira, Ayu; Purnamasari, Novia (Penerbit Widina, Widina Media Utama, 2025)
This study explores the implementation of Islamic Critical Thinking within inquiry-based learning models in pesantren (Islamic boarding schools). Amid the modernization of Islamic education, fostering critical reasoning rooted in Islamic values has become essential in shaping intellectual, reflective, and ethical students. Employing a qualitative field research approach including observation, in-depth interviews, and document analysis this study reveals that the integration of Islamic Critical Thinking values, such as open-mindedness, the pursuit of truth, and ethical dialogue, enhances students’ intellectual engagement and meaningful participation in classroom discussions. Teachers and pesantren leaders play a vital role in guiding students through a critical thinking process grounded in revelation and the Islamic scholarly tradition. The findings suggest that this approach not only strengthens cognitive skills but also nurtures the character of students who think wisely and critically. This conceptual study provides an epistemological framework for developing contemporary Islamic education models that remain responsive to modern challenges while rooted in core Islamic principles. It also calls for further empirical validation across diverse educational settings to assess the broader applicability and impact of integrating Islamic Critical Thinking in instructional practices.ABSTRAKPenelitian ini mengkaji penerapan Islamic Critical Thinking dalam model pembelajaran inkuiri di lingkungan pesantren. Dalam arus modernisasi pendidikan Islam, penguatan daya nalar kritis berbasis nilai-nilai Islam menjadi urgensi untuk membentuk generasi santri yang intelektual, reflektif, dan etis. Penelitian ini menggunakan pendekatan kualitatif melalui studi lapangan yang mencakup observasi, wawancara mendalam, dan dokumentasi. Hasil menunjukkan bahwa integrasi nilai-nilai Islamic Critical Thinking seperti keterbukaan berpikir, semangat mencari kebenaran, dan penghargaan terhadap etika dialog mampu mendorong respons intelektual yang lebih mendalam dan partisipasi santri yang bermakna dalam pembelajaran. Peran pengasuh dan guru pesantren sangat sentral dalam membimbing proses berpikir kritis yang berbasis pada wahyu dan tradisi ilmiah Islam. Penelitian ini menyimpulkan bahwa penerapan pendekatan ini bukan hanya mengembangkan aspek kognitif, tetapi juga membentuk karakter santri yang bijak dan berpikir tajam. Studi ini memberikan kontribusi konseptual dalam merumuskan kerangka epistemologis pendidikan Islam kontemporer, serta merekomendasikan riset lanjutan secara empiris di berbagai konteks pendidikan untuk menguji efektivitas pendekatan ini secara lebih luas.